FACILITATIVE LEADERSHIP AND SOCIAL COMMITMENT OF LOCAL ACTORS AS DETERMINANTS OF SUSTAINABILITY OF INTEGRATED ELDERLY SERVICES IN YOGYAKARTA CITY - Melisa Kristiana Octavia; Arif Wibowo (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Yogyakarta City faces challenges from an ageing population, including high life expectancy and increased elderly morbidity. The Integrated Elderly Service Program (LLT) was created to address fragmented services and promote “ageing in place”. This study examines the roles of facilitative leadership and local actors’ social commitment in sustaining LLT. Using a descriptive qualitative approach and the collaborative governance framework, data were collected through interviews, observation, and literature review. Informants were purposively chosen from government, non-government, and community stakeholders. The findings show that the Yogyakarta City Regional Development Planning Agency (Bappeda) provides strategic coordination and facilitative leadership, overcoming sectoral boundaries and enhancing collaboration. At the community level, program sustainability is strengthened by local actors’ intrinsic motivation and social ties. LLT’s ongoing success is driven by synergy between top-down strategic facilitation and bottom-up mobilization of social capital, resulting in “small wins” such as improved elderly health and better service coordination. LLT’s collaborative approach offers a valuable reference for developing adaptive, context-specific national regulations to address the complex dynamics of an ageing population.